Si and Ge based metallic core/shell nanowires for nano-electronic device applications. Issue 1 (December 2018) - Bhuyan, Prabal; Kumar, Ashok; Sonvane, Yogesh; Gajjar, P.; Magri, Rita; Gupta, Sanjeev
Abstract One dimensional heterostructure nanowires (NWs) have attracted a large attention due to the possibility of easily tuning their energy gap, a useful property for application to next generation electronic devices. In this work, we propose new core/shell NW systems where Ge and Si shells are built around very thin As and Sb cores. The modification in the electronic properties arises due to the induced compressive strain experienced by the metal core region which is attributed to the lattice-mismatch with the shell region. As/Ge and As/Si nanowires undergo a semiconducting-to-metal transition on increasing the diameter of the shell. The current-voltage (I-V) characteristics of the nanowires show a negative differential conductance (NDC) effect for small diameters that could lead to their application in atomic scale device(s) for fast switching. In addition, an ohmic behavior and upto 300% increment of the current value is achieved on just doubling the shell region. The resistivity of nanowires decreases with the increase in diameter. These characteristics make these NWs suitable candidates for application as electron connectors in nanoelectronic devices.